If it's not what You are looking for type in the equation solver your own equation and let us solve it.
94=2(u+17)
We move all terms to the left:
94-(2(u+17))=0
We calculate terms in parentheses: -(2(u+17)), so:We get rid of parentheses
2(u+17)
We multiply parentheses
2u+34
Back to the equation:
-(2u+34)
-2u-34+94=0
We add all the numbers together, and all the variables
-2u+60=0
We move all terms containing u to the left, all other terms to the right
-2u=-60
u=-60/-2
u=+30
| 2(x-3)^2+8=0 | | 2x-6+2x-6=2x-7 | | 10x-79=2x+59 | | 70/80=x/8 | | 2(x-3)2+8=0 | | 4/5x=45 | | 7080=x8 | | -10y=-1000 | | j/3+14=18 | | 2/7x=77 | | -8=1+5x-4 | | 11(x+10)-23=12x+220 | | 7/8x=96 | | 7x-2x-12=-2 | | 6+4(7x–2)=6+28x–8 | | 7/8x=78 | | z/7+9=-18 | | Y=x2-2x+5 | | 144-4x=112 | | 2s+1=1 | | 16/x=176/165 | | 2s1=1 | | x=74-(2x+7) | | 6x+5/2=39 | | r/12=0 | | t=45+(45/2)+(0.2*45) | | |2x+5|=23 | | t=(45/2)+(0.2*45) | | 2p−5=3 | | t=(45/0.2)+(0.2*45) | | 5x+14=4x+16 | | 13x+2=5x+24 |